Evaluation of carotid arterial elasticity in patients with obstructive sleep apnea hypopnea syndrome by two-dimensional speckle tracking imaging. Issue 51 (December 2017) - You, Manjie; Zhang, Li; Fang, Lingyun; Li, Jie; Xie, Mingxing
Abstract : Abstract: The objective is to evaluate carotid arterial elasticity in patients with obstructive sleep apnea hypopnea syndrome (OSAHS) by two-dimensional speckle tracking imaging (2D-STI). Sixty-two hospitalized patients with OSAHS and 20 healthy subjects were studied. The OSAHS patients were divided into 3 subgroups: a mild group, a moderate group, and severe group. All subjects underwent complete left common carotid artery (LCCA) examination by echo-tacking technique and 2D-STI. The stiffness parameter (β), elastic modulus (Eρ), stiffness β single pulse wave velocity (PWVβ), and arterial compliance (AC) were automatically calculated by echo-tracking technique. And the global and segmental peak systolic circumferential artery strain (CAS) values were made off-line using 2D-STI. The β, Ep, and PWVβ values of the carotid artery in the moderate and severe groups were greater than those in the control group ( P  < .05). In addition, the systolic peak global CAS and the segments between 5 and 7 o'clock in the moderate and severe groups were lower than those in the control group ( P  < .05). Compared with mild group, the β, PWVp, and Ep values of the carotid artery in the moderate and severe groups were higher ( P  < .05) and the systolic peak global CAS lower than in the control group ( P  < .05). The systolic peak global CAS was significantly inversely correlated with stiffness (β, r = − 0.61, P  < .05) and stiffness β single pulse wave velocity (PWVβ, r = −0.59, P  < .05). Through stepwise multiple linear regression analysis, age and SaO2 were the significant variables that determined the systolic peak global CAS 2D-STI provides a new method to investigate carotid arterial elasticity in patients with OSAHS.